Have the Links Between Natural Gas and Coal Prices Changed over Time? Evidence for European and Pacific Markets - Jerzy Rembeza; Dominik Katarzyński (Energies)
The relationships between the prices of major energy commodities have been a widely discussed topic in energy market analyses. This study examines whether the substantial changes observed in recent years have influenced the price linkages between coal and natural gas. By comparing selected price indices from European and Asian markets, we assess the evolving interdependencies between these fuels. The results indicate that the most significant changes in price linkages have occurred in European markets. Both VAR and ARDL model-based tests reveal a shift in the direction of causal relationships. Between 2006 and 2011, coal prices significantly influenced natural gas prices, with no strong evidence of reverse causality. However, in the more recent period (2018–2023), the relationship reversed—natural gas prices now have a significant impact on coal prices, while the reverse linkage has weakened. In Asian markets, the changes were less pronounced, particularly for Japanese import gas prices based on lagged average formulas. However, in the most recent period, a notable influence of Indonesian import gas prices on Australian coal prices emerged, mirroring trends observed in Europe. These findings highlight the increasing role of natural gas in shaping energy commodity prices, especially in Europe, where its growing importance in power generation has contributed to this shift. Additionally, the post-2018 period has been marked by significant supply disruptions, particularly in Europe, with geopolitical factors playing a crucial role in amplifying the importance of natural gas prices.